WOMEN AS THE SUBJECT OF ART AND THE OBJECT OF POPULAR CULTURE: A CRITICAL PERSPECTIVE ON ARTS MARKETING THROUGH MİLLİYET ART MAGAZINE (Third Sector Social Economic Review, 2023)
The research which is conducted within the framework of arts marketing and the relationship between art and society focuses on the objectification of women and their use as a kitsch element. The main objective of the research is to provide a comprehensive evaluation of the presence of women as subjects of art in art magazines, specifically their representation as objects of popular culture and kitsch, in parallel with the use of ""corrupted taste"" and ""fake aesthetics"" defined as ""kitsch"" by art magazines that bridge the gap between art and society.The research is based on the content analysis method, examining the elements of popular culture and women found in all the covers of Milliyet Sanat Magazine published between January 2002 and April 2023. Milliyet Sanat Magazine has been continuously published since 1972 and was chosen as it serves as an important medium of mass communication, playing a significant role in the communication process between art and society by featuring works, events, news, and articles related to all branches of art. The research discusses the use of kitsch on magazine covers as means of reaching wide audiences in the process of arts marketing, as well as the objectification of women and the emphasis on their sexual aspect. A total of 255 covers of Milliyet Sanat Magazine published in the last 20 years were analyzed through content analysis, focusing on art disciplines, women, and popular culture visuals and headlines. This research is important as it demonstrates the utilization of women as kitsch in the process of arts marketing, their dehumanization and objectification over the years, and explores the impact of this phenomenon on art, the relationship between art and society, and the perception of women in society.
Keywords: Arts Marketing Art; Kitsch; Popular Culture; Women; Milliyet Sanat Magazine